ARCHAEOLOGICAL POTENTIAL AND CULTURAL MEMORY: INVESTIGATING LESSER-KNOWN HERITAGE SITES IN MAYANG, MORIGAON - Pathak, Guptajit (International Journal of Research -GRANTHAALAYAH, 2022)
Mayang, in Assam’s Morigaon district, has enormous archeological potential that goes well beyond its common connotations of mysticism and black magic. This study explores the region’s lesser-known historical landmarks, emphasizing how tangible remnants like ruins, places of worship, oral traditions, and cultural artifacts add to a deeper comprehension of its past. The study makes the case that Mayang is important for recreating local histories that have been obscured by myths and inadequate documentation by placing the area within a larger archeological and cultural context. Through field observations, investigation of local documents, and contact with community elders, the study reveals how these places collectively contain layers of cultural memory that remain largely undiscovered. In order to reposition Mayang as a historically significant destination in Assam, the study also highlights the necessity of strategic heritage promotion by government agencies, academic institutions, non-governmental organizations, and local people. Mayang is positioned as a prospective multidisciplinary tourism hub because of its distinctive combination of cultural legacy, natural beauty, and ecological diversity, which is further strengthened by the existence of the endangered river dolphin in the Brahmaputra and the nearby Pobitora Wildlife Sanctuary. The area can develop into a significant cultural-historical tourism destination with the right infrastructure, conservation, and awareness-raising, supporting both sustainable development and the preservation of Assam’s rich legacy (Das, 2019, pp. 112-114).